Adverse events in hemodialysis: reports of nursing professionals - Sousa, Maiana Regina Gomes de; Silva, Ana Elisa Bauer de Camargo; Bezerra, Ana Lúcia Queiroz; Freitas, Juliana Santana de; Miasso, Adriana Inocenti (Revista da Escola de Enfermagem da USP, 2013)
This cross-sectional and quantitative study analyzed the knowledge of nursing professionals regarding Adverse Events (AE) in a hemodialysis unit of a teaching hospital. Data collection was performed between February and April 2011, based on interviews with 25 professionals. Data analysis identified 517 reports of 32 types of adverse events, of which the most commonly cited were: obstructed catheter, accidental withdrawal of the needle; and clotting of the extracorporeal system. Patient-related causes were mentioned in 42.8% of the reports. The main measures adopted were the implementation/ change of protocols and continuing education; the latter is the main suggestion for prevention. The results can contribute to a critical analysis of the quality of care in hemodialysis units, resulting in the development of interventions that help promote patient safety.